The hostile takeover dilemma: comparative analysis and regulatory recommendations for China - Kruszewska, Ewa Maria (2019)
Despite China’s impressive economic growth, many Chinese listed firms still suffer from weak financial performance. Corporate takeovers are often thought to be a cure for the problems of underperforming companies as they help to discipline managers ex-ante and allow to replace the board if it deviates from the firm’s interests. The effectiveness of the market for corporate control has, however, been challenged over the years; no single theory can nowadays definitively encapsulate the nature and effects of hostile takeovers, and the various empirical studies do not lead to firm conclusions regarding their alleged benefits.